Floral nectary structure, nectar presentation and morpho-anatomical analysis of male‐fertile and male‐sterile anthers in onion (Allium cepa, Amaryllidaceae) = Estructura del nectario floral, presentación del néctar y análisis morfo-anatómico de anteras de líneas androfértiles y androestériles en cebolla (Allium cepa, Amaryllidaceae) - Gonzalez, Ana Maria; Maldonado, Irma Beatriz; Galmarini, Claudio Romulo; Peralta, Iris Edith (Sociedad Argentina de Botánica, 2023)
Background and aims: The onion (Allium cepa var. cepa) is an allogamous species in which male-sterile lines have been developed. However, the structure of the flower and floral nectaries have only been briefly described. The objective of this study is to update the floral anatomy data, comparing the gynoecium and androecium of male-fertile and male-sterile lines, and to analyze the three-dimensional structure of the floral nectary. M&M: Conventional optical and scanning electron microscopy techniques were used. Results: Fertile and sterile male flowers have the same structural organization. The septal or gynopleural nectary is organized in three zones: 1) production area formed by the glandular tissue arranged radially in the septa of the ovary, 2) discharge zone: a small channel at the apex connects the nectariferous tissue with the pocket formed between the ovary wall and the overlying ridge, and 3) presentation and harvest zone, where the excreted nectar accumulates, formed between the widened base of the inner staminal filaments opposite the ovary. Conclusions: The only anatomical differences in the flowers sterile male lines are the lack of pollen production and the absence of dehiscence, despite having a normal stomium and anther wall. The floral nectaries of onion are a clear example of secondary presentation of nectar.